2020
DOI: 10.1016/j.cgh.2019.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Long-term Treatment of Chronic HBV Infection With Entecavir or Other Agents From a Randomized Trial in 24 Countries

Abstract: BACKGROUND & AIMS: Treatment of chronic hepatitis B virus (HBV) infection with entecavir suppresses virus replication and reduces disease progression, but could require lifelong therapy. To investigate clinical outcome events and safety associated with long-term treatment with entecavir, we followed up patients treated with entecavir or another standard-of-care HBV nucleos(t)ide analogue for up to 10 years. We assessed long-term outcomes and relationships with virologic response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
50
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 75 publications
(59 citation statements)
references
References 42 publications
0
50
0
Order By: Relevance
“…Our results were consistent with the results from the randomised, observational study of entecavir to assess long-term outcomes (REALM) study, which was conducted for 10 years with average follow-up period of 7 years that showed no difference between ETV and non-ETV antivirals in overall malignant neoplasm, deaths and HCC. 18 We also analysed non-HCC-related mortality and liver-related mortality to show in detail that there was no difference between the two groups. We also observed with interest that only a very few patients with chronic hepatitis or compensated cirrhosis died or received LT (eight patients, 0.3%) due to liver-related events other than HCC after treatment with highly potent antivirals such as ETV or TDF in the intermediate term.…”
Section: Discussionmentioning
confidence: 99%
“…Our results were consistent with the results from the randomised, observational study of entecavir to assess long-term outcomes (REALM) study, which was conducted for 10 years with average follow-up period of 7 years that showed no difference between ETV and non-ETV antivirals in overall malignant neoplasm, deaths and HCC. 18 We also analysed non-HCC-related mortality and liver-related mortality to show in detail that there was no difference between the two groups. We also observed with interest that only a very few patients with chronic hepatitis or compensated cirrhosis died or received LT (eight patients, 0.3%) due to liver-related events other than HCC after treatment with highly potent antivirals such as ETV or TDF in the intermediate term.…”
Section: Discussionmentioning
confidence: 99%
“…All eligible patients were randomly assigned (1:1) to receive either entecavir or an investigator-selected non-entecavir HBV nucleos(t)ide analogue and followed for up to 10 years. 14 The analysis included the data from patients treated with entecavir from 50 centres in 16 provinces in China.…”
Section: Realm Trial: a Global Randomized Controlled Trial (Rct)mentioning
confidence: 99%
“…The results of the REALM study have been published elsewhere, and revealed no significant differences in clinical endpoints between ETV and non-ETV nucleos (t)ide analogue treatment, and virologic response independent of treatment group was associated with a reduced risk of liver-related HBV disease progression (hazard ratio (HR): 0.09, 95% confidence interval (CI): 0.038-0.221) and HCC (HR: 0.03, 95% CI: 0.009-0.113). 24…”
Section: Patient Dispositionmentioning
confidence: 99%